METHODOLOGY OF USING ORIGINAL SOURCES IN TEACHING A FOREIGN LANGUAGE ON THE EXAMPLE OF THE FRENCH LANGUAGE - Meliboyeva Zarifa Umarovna (Zeta Repository, 2023)
Original documents designed with the communicative function of native French speakers in mind are important in language classes, as their use is suitable for teaching that is more oriented to real life and current events, more sensitive to motives. At the same time, it increases the student’s needs and interest in learning, and most importantly, makes the student more active and creative. The fact that authentic sources serve to convey authentic (or natural) communication helps to clarify one of the biggest goals of teaching French as a foreign language - learning to communicate naturally. In essence, these documents expose learners to aspects of language use that are not currently the subject of detailed description and yet need to be explored. After presenting the original document, this article will answer a series of questions that will help describe it, identify its characteristics and reasons for its use in the classroom.